PERUMUSAN STRATEGI BISNIS PENGIRIMAN DOKUMEN PT. DIANTA DAYA EMBARA JAKARTA - Olfebri Olfebri; Muhammad Harri Pasakti Nugroho; Andri Primadi (Institut Transportasi dan Logistik Trisakti, 2018)
PT. Dianta Daya Embara is one of the logistics company in Indonesia dealing with documents and package delivery. The purpose of the research is to figure out the strategy of the company to increase the number of document deliveries. The writer was using field research by observing the company while doing the internship program, interviewing the general manager, and spreading the questionnaire to the managers and supervisors of the company. SWOT analysis was used to analyse the data. The result of the EFI matrix shows that the strength of the company lies in the cleanliness of the warehouse. Based on EFE matrix, the opportunity of the company lies in the market place and business growth. Based on IE matrix, the company is in cell II in the position of growing and building. The study suggests the company to increase the number of delivery by giving additional delivery service for “express package.”